Analisis Intensitas Penggunaan Media Sosial Tik-Tok terhadap Interaksi Sosial di Madrasah Tsanawiyah Al-Jam’iyatul Washliyah Tembung - Sandi Kurnia Putri Tanjung; Masganti Sit; Ripho Delzy Perkasa (Journal on Education, 2023)
Research objectives: 1) To find out the social interaction of students with the use of tiktok at MTs Al-Washliyah Tembung, 2) to find out the social interaction of students without using tiktok at MTs Al-Washliyah Tembung and 3) to know the intensity analysis of the use of tiktok at MTs Al-Washliyah Tembung. A descriptive qualitative method of research using data analysis techniques the data gathering techniques in this study are observation, interviews, and documentation. After the data collection process is complete, then do data analysis. Data anlysis includes data reduction, data presentation, and verification. Based on the findings obtained: 1) Social interaction of students in the use of social media tiktok that occurs in the MTs Al-Washliyah environment, students really like tik tok social media because it can eliminate boredom and also be a fun activity for students who have tiktok, but they still want to socialize by interacting directly with friends at school. 2) The social interaction of students without the use of tiktok social media that occurs at MTs Al-Washliyah, is that there are some students who do not like tiktok because it disrupts study hours and there is a lack of interaction with friends at school, so there are some students who do not use tiktok, prefer to communicate directly with friends at school. 3) The intensity of using Tiktok social media, most of the students fall into the quite intense category in using Tiktok social media. Meanwhile, social interaction among students is included in a fairly good category. These results indicate that MTs Al-Washliyah students are quite good at social interaction. Based on the results of research conducted by researchers on tiktok users, out of a total of 71 students there were 47 people who used tiktok social media, while social interaction among students who were not tiktok users was included in the low category who preferred to focus on learning and interacting directly with friends at school which totaled 24 people.